Chin Necrosis as a Consequence of Prone Positioning in the Intensive Care Unit. (24th February 2015) - Bunker, Daniel Lee John; Thomson, Michael
Abstract : Pressure necrosis of the skin is a rarely reported avoidable complication of prone positioning that can be minimised by active collaboration between care teams. We report a case of pressure necrosis of the chin after prone ventilation in the intensive care setting. Such injuries pose a risk of infection, possible need for surgical intervention, and increased costs to the health care system. Pressure necrosis injuries should be diligently guarded against by the careful selection of support devices, frequent turning, and rigorous skin care to minimise extended external compression, particularly on the face and bony prominences.